Surgical treatment of hepatic Echinococcus granulosus - Waldemar Patkowski; Maciej Krasnodębski; Michał Grąt; Łukasz Masior; Marek Krawczyk (Gastroenterology Review)
Introduction : Infections caused by metacestode stage of the Echinococcus granulosus in humans result in disease named cystic echinococcosis. Aim: To present the outcomes of patients treated surgically for cystic echinococcosis of the liver. Material and methods : One hundred and nineteen patients treated in the period between 1989 and 2014 due to E. granulosus infection in the Department of General, Transplant, and Liver Surgery, Medical University of Warsaw were selected for this retrospective study. Diagnostic protocol included imaging examinations, i.e. ultrasonography and computed tomography of the abdomen. Blood samples where used to proceed sequential enzyme-linked immunosorbent assay (ELISA) using Em2plus antigen as well as polymerase chain reaction (PCR) to detect E. granulosus . Results : Surgery was the choice for treatment for almost all of the patients (98.3%). In 40 (34.2%) patients right hemihepatectomy, in 19 (16.2%) patients left hemihepatectomy, and in 21 (17.9%) patients bisegementectomy were performed. Postoperative complications occurred in 4 (3.4%) patients. In 3 patients biliary fistula requiring endoscopic treatment was observed, and 1 patient had subdiaphragmatic abscess successfully treated with drainage under ultrasound guidance. None of the patients died in the postoperative period, and the 1-, 5-, and 10-year survival rates were 100.0%, 90.9%, and 87.9%, respectively. Conclusions : Surgical treatment of the symptomatic cystic echinococcosis is the modality of choice for E. granulosus infection of the liver. Despite substantial development of diagnostic methods and new management opportunities, echinococcal infection still presents a challenge for epidemiologists, pharmacologists, and clinicists.